Identifikasi Illiberal Peacebuilding di Indonesia: Manajemen Konflik Pasca Otoritarian dalam Sengketa Lahan Sumatera Utara - Sandra Sandrina Sinaga; Adhi Cahya Fahadayna (Universitas Islam Darul Ulum Lamongan, 2024)
As one of the nations shifting from authoritarianism to democracy, Indonesia is not immune to the serious consequences of political and social instability. The deeply ingrained disputed land issues have gotten more vulnerable to worsen, given that the shift allows space for different economic and political interests to arise. With a focus on North Sumatra, this paper aims to identify the actions taken by local governments in the post-authoritarian era to address political challenges using Claire Smith's illiberal peacebuilding method, in contrast to Western-led or liberal mode of peace-building. The research method employs a qualitative approach with two main techniques; interviews with PTPN, BPN, and associated communities as well as literature reviews. Data were then analyzed using the Miles and Huberman qualitative analysis method which includes data condensation, data presentation, and drawing conclusions and verification. This paper discovered that local governments still resort to neopatrimonial practices, repressive policy making, and legal procedural manipulation to reduce the possibility of conflict against the local community who are now supposedly able to demand their rights to land ownership.